Encouraging wine storytelling in the tourist experience: A preliminary study - Santos, V. R.; Sousa, B. B.; Ramos, P.; Dias, Á.; Madeira, A. (Advances in Tourism, Technology and Systems. Smart Innovation, Systems and Technologies, 2022)
Wine tourism has long since ceased to be just a visit to wine producing regions and wineries, just to taste or buy wine. In fact, wine tourism has become more complex as a tourist product, due to the requirement of visitors to obtain a differentiated experience, composed of multiple elements Wine tourism activities consist of, above all, wine tastings and cellar, wine house and wine museum visits. Currently, and in the future, wine tourism has provided and boosted the creation of genuine and unique tourist experiences, more and more differentiated tailor-made. This preliminary approach aims to evaluate the role of wine storytelling as an antecedent in the wine tourism experience, namely on other constructs as winescape attributes, sensorial attraction, wine excitement and cultural experience. A range of practical implications are provided for wine tourism managers, marketers and wine guided tours namely on the importance on the training the storytelling skill by the wine cellars staff. The new vogue of wine tourism forces us to challenge and re-visit the power relationships that exist within contemporary tourism and the host–guest relationship. As an interdisciplinary approach, this research contributes positively to the development of theory in relationship marketing and tourism contexts in wine management (theoretical implications). At the end, guidelines for future work will be presented.